Development of balanced nutrient management innovations in South Asia: Lessons from Bangladesh, India, Nepal, and Sri Lanka - Kishore, Avinash; Alvi, Muzna; Krupnik, Timothy J.; International Maize and Wheat Improvement Center; International Rice Research Institute (International Food Policy Research Institute, 2019)
As part of the United States Agency for International Development (USAID)/Washington and Bill and Melinda Gates Foundation supported Cereal Systems Initiative for South Asia (CSISA) and the USAID/Nepal Seeds and Fertilizer (NSAF) project, the International Food Policy Research Institute (IFPRI) and the International Maize and Wheat Improvement Center (CIMMYT) organized a Regional Dialogue on September 5, 2019, in Kathmandu on “Innovations for Advancing Farmers’ Use of Balanced Nutrient Application in South Asia.” The aim of the event was to facilitate cross-country dialogues on efficient nutrient management in the region. The event saw participation from central and regional government representatives from policy and extension, private fertilizer companies and fertilizer federations, researchers from CGIAR centers, as well as representatives of the donor community. Participants came from India, Nepal, Bangladesh, and Sri Lanka. Interactive discussions were centred around three main themes: (a) cross-country learning and evidence sharing on policies and subsidies to promote balanced nutrient application, (b) market, policy, and product innovations in the fertilizer industry, and (c) learnings and insights on the development of innovative methods in research and extension targeted to farmers. This policy brief summarizes seven key lessons learned from the discussions in the workshop.